Impact of the tree component on N cycling in agroforestry systems under subhumid tropical conditions - Vanlauwe, Bernard; Sanginga, Nteranya (African Journals Online, 2004)
The tree component of agroforestry systems may interfere with N cycling in several ways. In alley cropping systems, first of all, the prunings added during the different activities have a certain biochemical quality and subsequent N release characteristics. Secondly, the quality of the complete organic matter pool or part of it and associated N release characteristics may be related to the quality of the added materials. Thirdly, the tree itself may recover part of the nutrients released from the added prunings. In this report, the impact of the tree component on the fate of freshly applied residue N and the relation between the demand for and supply of the residue N, or the degree of synchrony, are discussed. After application of the labeled residues, residue N incorporated in the particulate organic matter (POM) (the soil organic matter fractions larger than 0.053 mm), was shown to have the highest turnover rate. Crop uptake of applied residue N was low and especially limited to the first maize crop after residue addition. Substantial differences in hedgerow recovery of applied residue N were found between the Leucaena and Dactyladenia hedges. Though the Leucaena hedge recovered a significant proportion of the applied Leucatena residues, substantial amounts of added residue N remained in the soil profile in a bare microplot, during the first 7 weeks after residue addition. In the cropped microplot, maize removed all residue-derived mineral N from the soil profile in the Dactyladenia treatment and lowered the residue derived mineral N in the Leucaena treatment. Large discrepancies were observed between N release From the Leucaena surface litter and N uptake by the maize crop. However, after inclusion of the POM pool at the N supply side and hedgerow recovery and immobilization in the stable SOM at the N demand side, N supply seems to be relatively well balanced by N demand. Some possible research directions related to N cycling and synchrony in agroforestry systems and other improved cropping systems are highlighted.